The Murine Reg3a Stimulated by Lactobacillus casei Promotes Intestinal Cell Proliferation and Inhibits the Multiplication of Porcine Diarrhea Causative Agent in vitro - Bai, Yongfei; Huang, Yanmei; Li, Ying; Zhang, Bingbing; Xiao, Cuihong; Hou, Xilin; Yu, Liyun (Frontiers in Microbiology, 2021)
Lactobacillus casei (L. casei), a normal resident of the gastrointestinal tract of mammals, has been extensively studied over the past few decades for its probiotic properties in clinical and animal models. Some studies have shown that some bacterium of Lactobacillus stimulate the production of antimicrobial peptides in intestinal cells to clear enteric pathogens, however, which antimicrobial peptides is produced by L. casei stimulation and its function are still not completely understood. In this study, we investigated the changes of antimicrobial peptides expression after intragastric administration to mice the L. casei. The bioinformatics analysis uncovered there were 9 genes strongly associated with up-regulated DEGs. But only the antimicrobial peptide mReg3a gene of them was continuously up-regulated, which was also confirmed by qRT-PCR. We found out the mReg3a expressed in engineering E.coli promoted cell proliferation and wound healing proved by CCK-8 assay and wound healing assay. Moreover, the tight junction proteins ZO-1 and E-cadherin in mReg3a treatment group were significantly higher than that in the control group under the final concentration of 0.2mg/ml both in Porcine intestinal epithelial cells (IPEC-J2) and Mouse intestinal epithelial cells (IEC-6) (p < 0.05). Surprisingly, the recombinant mReg3a not only inhibited Enterotoxigenic Escherichia coli (ETEC), but also reduced the copy number of the piglet diarrheal viruses, porcine epidemic diarrhea virus (PEDV), porcine transmissible gastroenteritis virus (TGEV) and porcine rotavirus (PoRV), indicating the antimicrobial peptides mReg3a may be feed additives to resist the potential of the intestinal bacterial and viral diarrhea disease.